Dampak Implementasi Pendekatan Pembelajaran Berbasis Proyek Terhadap Perkembangan Karakter Anak - Djuningsih, Inggit; Apriyansyah, Chandra; Kurniawaty, Lia (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research aims to find out that the implementation of project-based learning (PjBL) has a positive impact in overcoming the challenges faced by the strawberry generation, such as concentration difficulties, technology dependence, and social distractions. Through project-based learning (PjBL), children are encouraged to be more active, collaborative, diligent and independent in the learning process. This can not only improve cognitive abilities, but also develop positive characters, such as creativity, innovation, empathy and responsibility. This research uses a social phenomenology and human behavior approach in order to focus on the experiences, perceptions, and strategies used by early childhood educators in overcoming the risks of Generation Strawberry. Qualitative data analysis techniques were applied using the help of Nvivo 15 software with data collection methods through interviews, observation and document analysis. The results showed that project-based learning (PjBL) is a promising learning approach in developing early childhood character and overcoming the challenges faced by the current generation.